Streptomyces spp. as a Biological Control Agent for Xanthomonas oryzae: A Strategy to Improve National Food Security; Review Article - Loekas Soesanto; Bahtiar Rahmadani; Nabila Revicha Setioningrum; Zidan Zifa Destafi; Abraham Febiano Kristian (Jurnal Biologi Tropis, 2026)
National food security faces serious challenges due to bacterial leaf blight in rice caused by Xanthomonas oryzae. This article aims to analyze the potential of Streptomyces spp. as biological control agents to suppress the development of this pathogen through a literature study approach. The method employed was a systematic review of national and international scientific journals discussing antagonistic mechanisms, secondary metabolite production, and the role of rhizobacteria in enhancing rice plant resistance. The findings indicate that Streptomyces spp. inhibit the growth of Xanthomonas oryzae by producing antibiotics, lytic enzymes, and inducing systemic resistance in rice plants. Furthermore, their application may reduce dependence on chemical pesticides, making them more environmentally friendly. Therefore, the utilization of Streptomyces spp. represents a promising biological strategy to improve rice productivity and strengthen national food security.